Do consumers' preferences for improved provision of malaria treatment services differ by their socio-economic status and geographic location? A study in southeast Nigeria - Tasie Nnenna G; Onwujekwe Obinna E; Uguru Nkoli P; Uzochukwu Benjamin S; Ezeoke Uche E (BMC, 2010)
Abstract Background Improvement of utilization of malaria treatment services will depend on provision of treatment services that different population groups of consumers prefer and would want to use. Treatment of malaria in Nigeria is still problematic and this contributes to worsening burden of the disease in the country. Therefore this study explores the socio-economic and geographic differences in consumers' preferences for improved treatment of malaria in Southeast Nigeria and how the results can be used to improve the deployment of malaria treatment services. Methods This study was undertaken in Anambra state, Southeast Nigeria in three rural and three urban areas. A total of 2,250 randomly selected householders were interviewed using a pre tested interviewer administered questionnaire. Preferences were elicited using both a rating scale and ranking of different treatment provision sources by the respondents. A socio-economic status (SES) index was used to examine for SES differences, whilst urban-rural comparison was used to examine for geographic differences, in preferences. Results The most preferred source of provision of malaria treatment services was public hospitals (30.5%), training of mothers (19%) and treatment in Primary healthcare centres (18.1%). Traditional healers (4.8%) and patent medicine dealers (4.2%) were the least preferred strategies for improving malaria treatment. Some of the preferences differed by SES and by a lesser extent, the geographic location of the respondents. Conclusion Preferences for provision of improved malaria treatment services were influenced by SES and by geographic location. There should be re-invigoration of public facilities for appropriate diagnosis and treatment of malaria, in addition to improving the financial and geographic accessibility of such facilities. Training of mothers should be encouraged but home management will not work if the quality of services of patent medicine dealers and pharmacy shops where drugs for home management are purchased are not improved. Therefore, there is the need for a holistic improvement of malaria treatment services.